Relationship between initial symptoms and the prognosis, sex, and demographic area of patients with COVID-19 - Oliván-Blázquez, Bárbara; Bartolomé-Moreno, Cruz; Gericó-Aseguinolaza, Junkal; Méndez-López, Fátima; Lerma-Irureta, David; Lamiquiz-Moneo, Itziar; Fernández-Martínez, Selene; Magallón-Botaya, Rosa (Frontiers in Medicine, 2022)
Background: Determining the initial symptoms and main identifiers of the prognosis of COVID-19 can be a key tool that especially helps primary care physicians. Therefore, the objective of this study was to analyse the prognosis of patients with COVID-19 according to baseline and predominant symptoms, age, and sex in two different demographic regions. Methods: All individuals from the urban health centre and the rural health centre were selected, who were over 18 years of age, had COVID-19 before March 2, 2021, and had been followed up by a primary care physician. Each patient included in the study was recruited in terms of sex, age at the point of the infection, type of contact, baseline, main and secondary symptomatology, emergency assistance, hospitalization, Intensive Care Unit (ICU) admission and death. Results: Two hundred nineteen and 214 subjects were recruited from a rural health and urban health centre respectively. Subjects from the rural area are significantly older, with a high proportion of men and reported significantly lower baseline and main symptoms than subjects from the urban area. Besides, the presence of fever and dyspnoea, either as initial or main symptom, are significantly associated with emergency assistance, hospitalization and death, independent of sex, age and demographic area. This type of illness was significantly reported on fewer occasions by the rural population than the urban population. Conclusion: The presence of fever and dyspnoea, both initial and main symptoms, is a factor to worse COVID-19 prognosis independent of age, sex and demographic area. Besides, women reported lower levels of fever and dyspnoea, as well as less emergency and hospital assistance and mortality. Subjects from the rural area seem to have had less access to medical care during the follow-up of their COVID-19 infection.